Survey Key Driver Analysis: Perhaps the Right Question Is, "Are We There Yet?". Issue 2 (29th June 2017) - Klein, Cameron; Synovec, Rob; Zhang, Haiyan; Lovato, Chris; Howes, John; Feinzig, Sheri
Abstract : In their focal article, Cucina, Walmsley, Gast, Martin, and Curtin (2017 ) raise an important and timely issue, but go too far in arguing that practitioners should abandon survey key driver analysis (SKDA) altogether. There are many valuable benefits to using SKDA, and rather than discontinuing the practice entirely, we suggest that a better approach is to focus on ways to make it even more valuable to organizations. It is true that this area is in need of further research, but instead of asking whether we are driving down the right road, perhaps the right question is, "Are we there yet?"